Linguopoeics of Magzhan Zhumabayev’s Poem “Tamerlane’s Word” and Its Translation into Russian and English Languages (Eurasian Journal of Philology Science and Education, 2025)
The article discusses the linguopoetics of Magzhan Zhumabaev’s famous poem “Tamerlane’s word” (textual and extra-textual) and the features of its translation into Russian and English. Poetic translation is the pinnacle of literary translation, in which each word and the number of words used by the author are counted in number, each linguistic and extralinguistic element has its own function, its place, explicit and implicit content. Therefore, not every translator dares to translate poetry. It is obvious that translating a lyric poet and symbolist such as Magzhan Zhumabaev is not so easy. Therefore, the purpose of the research article is to interpret and formulate the nature of the translation into Russian and English of the internal and external artistic image of the poem “Tamerlane’s word”, the essence of translation transformations that occurred during the translation process.The article is based on the reflections of scientists on the “possibility and impossibility” of poetic translation – one of the “eternal” problems, which, having not found a solution in the world of translation science, has caused a lot of discussion. Two versions of the Russian translation and the English translation are compared with the original, analyzed at the textual and extra-textual level, and possible predictions are made. Changes in translation are considered from the point of view of the impact on the thoughts and intentions of the original author and wording. This is the practical value of the study.As a result, it is concluded that a poetry translator must have not only the general linguistic competence of the original language and the target language, but also the literary and poetic language and style of both sides, a system of cultural values, history, and even study in advance the life and work of the author, the purpose of writing this poem, the characteristics of his time and society, have poetic abilities.Keywords: Magzhan Zhumabaev, poetry, poetic translation, linguopoetics, means of artistic expressions.